2002
DOI: 10.1046/j.1523-5378.2002.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Strain and the Pattern of Gastritis Among First‐Degree Relatives of Patients with Gastric Carcinoma

Abstract: The results of this study are not consistent with the hypothesis that specific virulence factors or similar H. pylori strains correlate with a specific histologic pattern or outcome even among those sharing the same environment in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Indirect evidence of transmission within sibships has been reported from a low-income country by using concordance in urea breath tests (14). In addition, clustering of strains in sibships has been demonstrated before (16,20,22,38,39).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Indirect evidence of transmission within sibships has been reported from a low-income country by using concordance in urea breath tests (14). In addition, clustering of strains in sibships has been demonstrated before (16,20,22,38,39).…”
Section: Discussionmentioning
confidence: 88%
“…It has previously been suggested that children are colonized by the mother's strain more often than the father's (16). However, both father-offspring and mother-offspring strain concordances have been reported repeatedly by studies using molecular typing (2,7,11,16,20,22,24,33,38,39). Epidemiologic data also indicate that the father has some role in children's acquisition of H. pylori (30,35).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Together, these data make it very unlikely that the cag PAI is solely responsible for tropism to a particular region of the stomach, although it may affect colonization levels. Although it is not clear whether bacterial genotypes determine infection patterns (36), some strains have a specific and consistent tropism during animal infections (1). We were not able to find any genes that were present or absent exclusively in isolates obtained from a particular region of the stomach, although such negative results might have been expected given our small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is acquired during childhood by intrafamilial transmission [3,4], and infection continues lifelong in the absence of antibiotic therapy. It has been postulated [5] that this lifelong association is accompanied by the selection of well-adapted, host-specific variants with particular patterns of expression of adhesins [6,7] and other surface molecules [8,9].…”
Section: Introductionmentioning
confidence: 99%